Pengaruh Edukasi Kesehatan Terhadap Perubahan Perilaku Hidup Bersih Dan Sehat (PHBS) - Yona Sahalessy; Rony Alexander Latumenasse; Sitti Johri Nasela; Theofilya Amandya Kissya; Masrikat Maya Diana Claartje (Barongko: Jurnal Ilmu Kesehatan, 2026)
Clean and Healthy Living Behavior (PHBS) is a strategic effort to improve public health. Low implementation of PHBS remains a public health problem, contributing to increasing morbidity. Health education is an effective promotive approach to encourage behavior change in the community. This study aims to determine the effect of health education on changes in clean and healthy living behavior. The study used a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 60 respondents selected using a purposive sampling technique. The research instrument was a PHBS questionnaire. Data were analyzed descriptively and comparatively. The results showed an increase in PHBS behavior after health education. It was concluded that health education has an effect on changes in clean and healthy living behavior.